Clinical Practice Guideline: Opioid Prescribing for Analgesia After Common Otolaryngology Operations. (April 2021) - Anne, Samantha; Mims, James "Whit"; Tunkel, David E.; Rosenfeld, Richard M.; Boisoneau, David S.; Brenner, Michael J.; Cramer, John D.; Dickerson, David; Finestone, Sandra A.; Folbe, Adam J.; Galaiya, Deepa J.; Messner, Anna H.; et al.
Objective: Opioid use disorder (OUD), which includes the morbidity of dependence and mortality of overdose, has reached epidemic proportions in the United States. Overprescription of opioids can lead to chronic use and misuse, and unused narcotics after surgery can lead to their diversion. Research supports that most patients do not take all the prescribed opioids after surgery and that surgeons are the second largest prescribers of opioids in the United States. The introduction of opioids in those with OUD often begins with prescription opioids. Reducing the number of extra opioids available after surgery through smaller prescriptions, safe storage, and disposal should reduce the risk of opioid use disorder in otolaryngology patients and their families. Purpose: The purpose of this specialty-specific guideline is to identify quality improvement opportunities in postoperative pain management of common otolaryngologic surgical procedures. These opportunities are communicated through clear actionable statements with explanation of the support in the literature, evaluation of the quality of the evidence, and recommendations on implementation. Employing these action statements should reduce the variation in care across the specialty and improve postoperative pain control while reducing risk of OUD. The target patients for the guideline are any patients treated for anticipated or reported pain within the first 30 days after undergoing common otolaryngologic procedures. The target audience of the guideline is otolaryngologists who perform surgery and clinicians who manage pain after surgical procedures. Outcomes to be considered include whether the patient has stopped using opioids, has disposed of unused opioids, and was satisfied with the pain management plan. The guideline addresses assessment of the patient for OUD risk factors, counseling on pain expectations, and identifying factors that can affect pain duration and/or severity. It also discusses the use of multimodal analgesia as first-line treatment and the responsible use of opioids. Last, safe disposal of unused opioids is discussed. This guideline is intended to focus on evidence-based quality improvement opportunities judged most important by the guideline development group. It is not a comprehensive guide on pain management in otolaryngologic procedures. The statements in this guideline are not intended to limit or restrict care provided by clinicians based on their experiences and assessments of individual patients. Action Statements: The guideline development group made strong recommendations for the following key action statements: (3A) prior to surgery, clinicians should identify risk factors for opioid use disorder when analgesia using opioids is anticipated; (6) clinicians should advocate for nonopioid medications as first-line management of pain after otolaryngologic surgery; (9) clinicians should recommend that patients (or their caregivers) store prescribed opioids securely and dispose of unused opioids through take-back programs or another accepted method. The guideline development group made recommendations for the following key action statements: (1) prior to surgery, clinicians should advise patients and others involved in the postoperative care about the expected duration and severity of pain; (2) prior to surgery, clinicians should gather information specific to the patient that modifies severity and/or duration of pain; (3B) in patients at risk for OUD, clinicians should evaluate the need to modify the analgesia plan; (4) clinicians should promote shared decision making by informing patients of the benefits and risks of postoperative pain treatments that include nonopioid analgesics, opioid analgesics, and nonpharmacologic interventions; (5) clinicians should develop a multimodal treatment plan for managing postoperative pain; (7) when treating postoperative pain with opioids, clinicians should limit therapy to the lowest effective dose and the shortest duration; (8A) clinicians should instruct patients and caregivers how to communicate if pain is not controlled or if medication side effects occur; (8B) clinicians should educate patients to stop opioids when pain is controlled with nonopioids and stop all analgesics when pain has resolved; (10) clinicians should inquire, within 30 days of surgery, whether the patient has stopped using opioids, has disposed of unused opioids, and was satisfied with the pain management plan.